Макроскопическая модель трехфазной термодинамической системы переменной массы - Степанова, А. И. (Енергетика і автоматика, 2017)
MACROSCOPІC MODEL OF THREE-PHASETHERMODYNAMIC SYSTEM OF VARIABLE MASSА. StepanovаA necessary component of the overall process of improving energy technology systems in utility and industrial power system is its thermodynamic optimization. Among its main tasks include selection criteria for evaluating the effectiveness of the system, which can serve as optimization objective, the choice of research methods and the choice of optimization techniques, which include obtaining the necessary equations used to solve optimization problems.Modern systems flue gas heat recovery power plants such as boilers aggregates and glass melting furnaces etc. Are used as coolants typically multiphase medium with variable concentrations of one or more phases. Such heat transfer fluids are in heat recovery systems, such as flue gases and dusty air, containing water vapor. The degree of dust and moisture during the steam-gas mixture passing through the heat recovery system can be changed in various ranges depending on the purpose and design of such a system. So when deep heat recovery Flue Gas heating boiler flue gas absolute humidity in the heat exchanger at low loads can vary boiler 2.5 ... 4 times, and in the heat-recovery systems, designed for heating and humidifying the air blast boiler installations, the absolute humidity may vary dozens of times. On steklovyrabatyvayuschih enterprises in the furnace off-gases present a significant amount of contaminants. These components whose contents in industrial furnaces varies from 50 to 1000 mg / m3, include solid technological entrainment (sand, sodium, aluminum, carbon black, etc.), And the corrosive compounds of nitrogen, sulfur, carbon, fluorine and other harmful and chemically aggressive substances in the gaseous phase. The degree of dust off-gases in the process of passing through a heat recovery system changes due to the formation of a layer of slag deposits on the heat exchange surfaces of exchangers, which significantly reduces their effectiveness.In such multiphase flow exist simultaneously different thermodynamic forces and irreversible flow that lets you search for functional relationships needed to solve optimization problems using methods of thermodynamics of irreversible processes, together with exergy methods. In this paper we formulated the macroscopic behavior of a three-phase thermodynamic model of the system of variable mass when the concentration of one of the phases. The thermodynamic system is considered as microinhomogeneous medium comprising three phases: gas, solid particles and water vapor. We derive the equation for the change in mass of three-phase thermodynamic system when the concentration of the third phase. For local differential equation Exergy balance three-phase system with a variable concentration of one phase of the phases are used the equations of motion, balance, kinetic, potential, and full of internal energy, enthalpy balance equation and the Gibbs equation. The resulting equation allows for exergetic loss in a thermodynamic system related to thermal conductivity and viscosity of the phases, interfacial friction and heat exchange between phases. The equation can be used to solve optimization problems in heat recovery systems that use as coolants multiphase environment variable concentrations.